Oligodendrocyte arrangement, identification and morphology in the developing superior olivary complex - Zacher, Alina Carola; Grabinski, Melissa; Console-Meyer, Laura; Felmy, Felix; Pätz-Warncke, Christina (Frontiers in Cellular Neuroscience, 2025)
Oligodendrocytes provide myelination, metabolic and developmental support for neurons and circuits. Within the auditory superior olivary complex (SOC), relevant for sound localization and spectro-temporal integration, oligodendrocytes are fundamental for fast neuronal communication and accurate timing of sound signals. Despite their important role in function and development, an assessment of their developmental arrangement and morphology is missing for the SOC. Here, immunofluorescence labeling and single cell electroporation was used to quantify their distribution, identification and morphology between postnatal day (P) 5 and ~ P54 in the SOC of Mongolian gerbils (Meriones unguiculatus). Oligodendrocytes show developmental, region-specific accumulations, redistributions and density profiles. Their identification by Olig2 and SOX10 appears age specific, while myelinating oligodendrocytes are detected by co-labeling with S100 irrespective of age. Comparison of oligodendrocyte density and identification between mature gerbil and Etruscan shrew (Suncus etruscus), revealed species-specific differences. Morphologically, the number of myelinating processes decreased, while process length, diameter and coverage area of oligodendrocytes increased during development. Together, oligodendrocyte developmental alterations occur at moments of SOC circuit refinement supporting functions beyond myelination.